Irrational Ideas among Teenagers Students with Sons of Martyrs and Ordinary in Schools of Lattakia City - A Field Comparative Study (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
The research aimed to identify the degree of existence the irrational ideas among teenagers students with sons of martyrs and ordinary in schools of Lattakia City, and to identify the differences in the degree existence of the irrational ideas between Teenagers Ordinary Students and Teenagers Sons of Martyrs Students and in Lattakia City, also to identify the differences in degree existence of the irrational ideas according to the following variables (kind of sex, arrangement of congenital), To achieve the object of the research use Suleiman Al- Rehany measure for irrational ideas, has been included (48) phrase. Then after were confirmed validity and reliability was applied to a sample of (256) teenagers students (86 sons of martyrs and 166 ordinary) in Schools of Lattakia city for the academic year 2020/2021.The most important findings of the research:• The degree of existence the irrational ideas among teenagers students with sons of martyrs in schools of Lattakia City was high• The degree of existence the irrational ideas among teenagers oordinary students in schools of Lattakia City was middle degree.• There were differences of statistically significant between Teenagers Students with Sons of Martyrs and Ordinary in Schools of Lattakia City on irrational ideas measure in favor of teenagers students with sons of martyrs.• No statistically significant differences among Teenagers Ordinary Students on irrational ideas measure according to the variable (arrangement of congenital), while there are statistically significant differences according to variable (kind of sex) in favor of the females.• No statistically significant differences among teenagers students with sons of martyrs on irrational ideas measure according to the variable (kind of sex and arrangement of congenital).    In the light of the researcher a recommendations including: Developing the Rational Ideas skills for the teenagers students with sons of martyrs, Developing the positive thinking among the teenagers students, also presenting the consolidation for the teenagers females, and rising another studies as the relation between  the Rational and Irrational Ideas and another variables.